Predominant expression and activation-induced tyrosine phosphorylation of phospholipase C-gamma 2 in B lymphocytes. - Coggeshall, K M (1992)
The triggering of T- or B-cell antigen-specific receptors is accompanied by rapid tyrosine phosphorylation of distinct cellular substrates, one of which is the gamma 1 isoform of inositol phospholipid-specific phospholipase C (PLC-gamma 1). This phosphorylation event, mediated by a putative protein tyrosine kinase coupled to the antigen receptor, probably stimulates the enzymatic activity of PLC-gamma 1, thereby promoting inositol phospholipid hydrolysis and other downstream signal transduction events. Recently, another ubiquitously expressed PLC isoform, PLC-gamma 2 (which shares 50.2% amino acid homology with PLC-gamma 1), has been identified. PLC-gamma 2-specific antibodies were used to evaluate the distribution and potential signaling role of this isoform in lymphocytes. Here, we report that, in contrast to T lymphocytes that express predominantly PLC-gamma 1, the major isoform expressed in murine and human resting B cells is PLC-gamma 2. Among B-cell tumor lines, all five murine B-lymphoma lines tested and one of six human B-lymphoblastoid cell lines also expressed predominantly PLC-gamma 2. However, three other human lines preferentially expressed PLC-gamma 1, and two others displayed similar levels of the two PLC-gamma isoforms. Furthermore, the triggering of B-cell surface immunoglobulin by anti-receptor antibodies was accompanied by a rapid tyrosine phosphorylation of PLC-gamma 2, which peaked after 5 min of stimulation. Conversely, and in agreement with recent reports, triggering of the T-cell antigen receptor complex led to the predominant phosphorylation of PLC-gamma 1 on tyrosine. These findings identify PLC-gamma 2 as a substrate for a B-cell putative protein tyrosine kinase coupled to the antigen receptor and suggest that its tyrosine phosphorylation constitutes a critical and early event in B-cell activation and, furthermore, that PLC-gamma 1 and PLC-gamma 2 may participate in similar but distinct signal transduction pathways in lymphocytes.